Case report: marantic endocarditis in renal cell carcinoma: nephrectomy a treatment. Issue 11 (4th November 2021) - Harris, Andrew Z; Ternouth, Ian; Lallu, Bhavesh D
Abstract: Background: Marantic endocarditis (non-bacterial thrombotic endocarditis) is a rare condition that involves non-infectious thrombotic lesions typically of the aortic and mitral valves. It is predominantly associated with malignancy and less commonly systemic lupus erythematosus. In this case, we report a patient with marantic endocarditis secondary to a renal cell carcinoma that was successfully treated with nephrectomy and anticoagulation. Case summary: A 65-year-old male patient with embolic signs and symptoms was found to have non-infective thrombotic vegetations on three cardiac valves through transoesophageal echocardiography. Computed tomography revealed a 70 mm renal mass that confirmed to be a grade two clear-cell renal cell carcinoma. Nephrectomy and anticoagulation led to resolution of the embolic symptoms and of the valvular vegetations. Discussion: The diagnosis of marantic endocarditis requires high clinical suspicion in a patient who presents with features of embolization. Incidence is highest in patients with an underlying malignancy, particularly adenocarcinoma. This case highlights the importance of echocardiography in diagnosis, removal of the source of thrombus, and prompt treatment with anticoagulation.